Incidence and risk factors of cerebral sinovenous thrombosis in infants. (27th January 2021) - Sorg, Anna‐Lisa; Von Kries, Rüdiger; Klemme, Mathias; Gerstl, Lucia; Beyerlein, Andreas; Lack, Nicholas; Felderhoff‐Müser, Ursula; Dzietko, Mark
Abstract : Aim: To describe the incidence of term and preterm neonatal cerebral sinovenous thrombosis (CSVT) and identify perinatal risk factors. Method: This was a national capture‐recapture calculation‐corrected surveillance and nested case–control study. Infants born preterm and at term with magnetic resonance imaging‐confirmed neonatal CSVT were identified by surveillance in all paediatric hospitals in Germany (2015–2017). Incidence was corrected for underreporting using a capture‐recapture method in one federal state and then extrapolated nationwide. We reviewed PubMed for comparisons with previously reported incidence estimators. We used a population‐based perinatal database for quality assurance to select four controls per case and applied univariate and multivariable regression for risk factor analysis. Results: Fifty‐one newborn infants (34 males, 17 females; 14 born preterm) with neonatal CSVT were reported in the 3‐year period. The incidence of term and preterm neonatal CSVT was 6.6 (95% confidence interval [CI] 4.4–8.7) per 100 000 live births. Median age at time of confirmation of the diagnosis was 9.95 days (range 0–39d). In the univariate analysis, male sex, preterm birth, hypoxia and related indicators (umbilical artery pH <7.1; 5‐minute Apgar score <7; intubation/mask ventilation; perinatal asphyxia), operative vaginal delivery, emergency Caesarean section, and pathological fetal Doppler sonography were associated ( p <0.05) with neonatal CSVT. Multivariable regression yielded hypoxia (odds ratio=20.3; 95% CI 8.1–50.8) as the independent risk factor. Interpretation: Incidence of neonatal CSVT was within the range of other population‐based studies. The results suggest that hypoxia is an important perinatal risk factor for the aetiology of neonatal CSVT.